The Effectiveness of Range of Motion (ROM) on Increasing Muscle Strength in Stroke Patients: Literature Review - Indriana Noor Istiqomah; Syaifuddin Kurnianto; Nur Khovifah; Achlish Abdillah (Nursing and Health Sciences Journal (NHSJ), 2022)
Stroke is one of the health problems that cause movement disorders in sufferers due to decreased loss or decreased muscle function. Range of motion exercise is thought to improve movement function in stroke patients. Aim: The purpose of this study was to determine the effectiveness of a range of motion (ROM) on muscle strength in stroke patients. Thus, the authors discussed the literature review on the effectiveness of a range of motion (ROM) on muscle strength in stroke patients. Method: A systematic search was conducted in the following three databases: PUBMED, PLOS ONE, EBSCO, and GOOGLE SCHOLAR using the keywords “Stroke” AND “Range Of Motion” AND “Muscle Strength.”. Result: There are 417 articles in the Pubmed, Plos One, Ebsco, and Google Scholar databases, but only eight articles meet all criteria, including search and review. The results of statistical tests in eight literature show that most of the effects of a range of motion exercises on increasing muscle strength in stroke patients are carried out 1-2 times a day, and the duration of each extremity is 15-20 minutes per session, performed two times a day for six days. Discussion: Performing ROM exercises for stroke patients must be adjusted to the recommendations for both the type and time of implementation. It aims to maintain or increase muscle mass and muscle tone of patients with stroke who have decreased muscle strength. Conclusion: Range of motion exercise affects increasing muscle strength in patients with stroke.